Contribution of mineralogical sedimentological and geochemical characteristics of deltaic deposits in the 137Cs sediment concetration - ΜΑΡΓΑΡΙΤΗΣ, Ι. (Bulletin of the Geological Society of Greece, 2001)
This parer provides a review of the factors governing 137Cs sorption in sediments. We have specially focused in the correlation between sorption and the sedimentological mineralogical and geochemical characteristics of the sediments. Literature conclusions in experimental as well as field studies on 137Cs sorption is that 137Cs is strongly correlated with the < 20μηι fraction of the sediment as well as illite content. Other clay minerals such as smectite, kaolinite and chlorite sorb 137Cs in a lesser degree. Furthermore organic material and Fe-Mn hydroxides, act like sorptive surfaces. Our data on 137Cs activity variation based on field studies from deltaic deposits (Arachthos delta, Amvrakikos gulf, Greece)is also discussed. The results of this studies confirm the above mentioned, since 137Cs activity is strongly correlated with the clay fraction and the illite content,while a lesser correlation is indicated for total organic carbon Fe and Mn content of the sediments.